BS EN ISO 21219-10. Intelligent transport systems. Traffic and travel information (TTI) via transport protocol experts group, generation 2 (TPEG2). Part 10. Conditional access information (TPEG2-CAI) (28th July 2020) - British Standards Institution,
No abstract available